PENDIDIKAN AGAMADALAM BINGKAI ISLAM DI NUSANTARA - Abdullah B (IAIN PAREPARE, 2016)
Religious education by using the approach of the study of Islam Nusantara is the concept of education about Islam by making the local culture as a medium. Islam Nusantara is a religious concept launched by religious leaders to eliminate the stigma that everything that comes from the Arabic does not make it absolutely true. Islam and the Arabs are not the same thing but two different things though in the beginning, Islam developed in the Arab lands and holy man who was elected as a messenger of God was born as a descendant of the Arabs. Islam Nusantara none other than the understanding, practice, and application of Islamic jurisprudence mu'amalah segment as a result of a dialectic between the texts, the shari'ah, and 'urf, culture and realities in the archipelago. This article examines the linkage between Islamic education and its relevance in affirming national identity and diversity. The analysis used in this paper is an analysis of the historical and material context of Islamic religious education by using literature reviews.